Education in Kazakhstan in the post-war years - Tursynbayev, Olzhas; Ybyraimzhanov, Kalibek; Bekish, Azamat; Nurman, Sholpan; Aubakirova, Assem (Journal of Education Culture and Society, 2024)
Aim. The purpose of the study was to study approaches to the resumption of an effective educational process in the Kazakh SSR after the end of the World War II. The study of the approaches to restoration and improvement of the educational system in post-war Kazakhstan is relevant in today’s conditions, when the educational environment of Kazakhstan faces a number of challenges that require its reform. Methods. Various research methods were used in the scientific work, in particular, analysis, synthesis, comparison, deduction, generalisation. Results and conclusion. As a result, the state of the educational environment in Kazakhstan was studied immediately after the end of the war. The approaches of state bodies to the regulation of educational public relations are considered, taking into account the conditions of that time. There was a significant increase in the number of schools and other educational institutions, which contributed to the development of educational infrastructure. It is proved that the priority specialties for the state were those that contributed to the implementation of construction and economic activities. Based on this, it was possible to reveal the main advantages in reforming education, which contributed to improving the quality of knowledge in schools, universities and technical schools. Cognitive value. The value of the results obtained is both scientific and practical. Accordingly, the first provides a deepening of knowledge regarding the historical process of the formation of the educational environment in Kazakhstan, and the second allows us to determine the most effective ways to revive education in society.